Practices of coexistence and coexistence in Wayúu children: an analysis of your particular games/Prácticas de convivencia y coexistencia en niños Wayúu: un análisis de sus juegos particulares (Encuentros, 2018)
The objective of this article is to analyze the practices of coexistence and social coexistence of the Wayúu community, practiced through their traditional children’s games. It is a qualitative research, of descriptive type, modality of “Analysis of a particular experience”. School children between 6 and 12 years of age participated. We applied the “Matrix of observation and registration of the coexistence behaviors manifested by wayúu children in their children’s games”, designed by the authors. Three traditional games were found that generate coexistence and coexistence in the community: Wayuunkerra, the choocho and the toco; but it is the games of his community like Wayuunkerra and Jirokainay, which generate more behaviors of coexistence than the western games adopted.Key words: Wayuu, Children’s games, Community, Coexistence, Coexistence.